2008
DOI: 10.1103/physrevlett.101.013903
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Multivortex Solitons in Photonic Lattices

Abstract: We report on the first observation of topologically stable spatially localized multivortex solitons generated in optically induced hexagonal photonic lattices. We demonstrate that topological stabilization of such nonlinear localized states can be achieved through self-trapping of truncated two-dimensional Bloch waves and confirm our experimental results by numerical simulations of the beam propagation in weakly deformed lattice potentials in anisotropic photorefractive media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…However, more recently both in optics [28,29] and in BEC [30,31] (so far in the absence of the lattice for the latter case), the study of higher charge vortices has been of interest. In particular, in the emerging area of hexagonal [21,32] and honeycomb [20] lattices, it has been predicted [33,34] and experimentally observed [35] very recently that a higher-order vortex with topological charge S = 2 is more stable than a fundamental vortex with unit charge (S = 1) when self-trapped with a focusing nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently both in optics [28,29] and in BEC [30,31] (so far in the absence of the lattice for the latter case), the study of higher charge vortices has been of interest. In particular, in the emerging area of hexagonal [21,32] and honeycomb [20] lattices, it has been predicted [33,34] and experimentally observed [35] very recently that a higher-order vortex with topological charge S = 2 is more stable than a fundamental vortex with unit charge (S = 1) when self-trapped with a focusing nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of groups have been studying the diffraction of OV through the photonic lattices to generate solitons [7][8][9][10][11][12]. Terhalle et al [7] reported the generation of multivortex solitons when vortex beam diffract from laser-induced photonic lattice in a strontium barium niobate crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Terhalle et al [7] reported the generation of multivortex solitons when vortex beam diffract from laser-induced photonic lattice in a strontium barium niobate crystal. Alexander et al [11] used triangular photonic lattice to demonstrate the self-trapped states of light in the form of multivortex localised states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further experimental studies in two-dimensional square lattices include DVSs that bifurcate from the second linear band [110,111], and with topological charge equal to two [112]. DVSs have also been observed in hexagonal lattices, including discrete multivortex solitons (several vortices inside the cluster of excited waveguides) [113], DVSs with topological charge two [114], and single DVSs [115]. Some of the observed discrete vortex solitons in Refs.…”
Section: Vorticesmentioning
confidence: 99%